Analisis Pendapatan Usahatani Tanaman Cabai Di Desa Taraitak Satu Kecamatan Langowan Utara - Manampiring, Evita Rike; Benu, Olfie Liesje Suzana; Sendow, Martha Marejke (Sam Ratulangi University, 2023)
This study aims to determine the income of chili farming in Taraitak Satu Village, North Langowan District. This research was carried out for 3 months, starting from March 2021 to May 2021, starting from the preparation of the research report to the preparation of the research report. The research location is located in Taraitak Satu Village, North Langowan District. The data analysis method used in this research is descriptive data analysis. The results of the analysis of chili farming income analysis in Taraitak Satu Village can be concluded that the average income of chili farmers with an average area of 1 Ha is Rp. 70,684,259/Ha, with a production cost of Rp. 12,102,662/Ha so that the average income of chili farmers is Rp. 58,581,597/Ha.